Slot stitching for longitudinal joint separation repairs. (15th July 2016) - Chen, Dar Hao; Choi, Pangil; Chen, Kuan Yu; Won, Moon
Highlights: Slot stitching is able to repair lane separations. Slot stitching provides 28% improvement in LTE after 4 years of service. The backfill materials should be low-shrinkage and low-CoTE. Abstract: Lane separations at longitudinal joints not only allow water to infiltrate into layers under the concrete slabs and deteriorate slab support, but degrade load transfer efficiency (LTE) along longitudinal joints, resulting in an increase in load-related stresses in concrete slabs and poor performance of pavement. Slot stitching provides one of the more efficient methods to restore pavement structural capacity due to lane separations. In 2010, three slot stitching design configurations were implemented on US-75 in Sherman, Texas, which experienced lane separations as well as faulting along the longitudinal construction joint. After the dowel bars were installed, the ultra rapid repair method with the use of high early strength, low shrinkage, and low coefficient of thermal expansion (CoTE) backfill materials was utilized to minimize the traffic interruption and to restore the elevation. For measuring the effectiveness of the repair method, LTE at longitudinal joints was evaluated using Falling Weight Deflectometer (FWD). Testing results in this paper demonstrate the effect of slot stitching design, or more specifically the number of slot stitching in a slab and/or bar size, on improving LTE by providing before-and-after LTE measurements and detailed material information. In particular, the design configuration with 5 #8 bars (25.4-mm diameter) was the most cost-effective and efficient, with about 28% improvement in LTE after more than 4 years of service. Moreover, three design configurations with the use of low-shrinkage, low-CoTE backfill materials were demonstrated to improve LTE substantially, with an average increase from 45% to 74%.